Accelerated model of lupus autoimmunity and vasculopathy driven by toll-like receptor 7/9 imbalance. Issue 1 (14th May 2018) - Liu, Yudong; Seto, Nickie L; Carmona-Rivera, Carmelo; Kaplan, Mariana J
Abstract : Objectives: Activation of endosomal toll-like receptor (TLR)7 or TLR9 has been proposed as a critical step for the initiation and development of SLE. Traditional spontaneous lupus models normally introduce multiple risk alleles, thereby adding additional confounding factors. In the induced lupus models, the role of TLR9 remains unclear. In the present study, we explored the role of an imbalance between TLR7 and TLR9 pathways in the pathogenesis of lupus and its associated vasculopathy using the imiquimod model in TLR9 KO/B6 background. Methods: Wild type (WT) and Tlr9 -/- mice were epicutaneously treated with imiquimod cream 5% on both ears three times per week for indicated times. At euthanasia, mice were analysed for organ involvement, endothelium-dependent vasorelaxation, serum autoantibodies, and innate and adaptive immune responses. Results: Compared with the lupus-like phenotype that develops in imiquimod-treated WT mice, Tlr9 -/- mice exposed to imiquimod have increased severity of autoimmunity features and inflammatory phenotype that develops at earlier stages. These abnormalities are characterised by enhanced TLR7 expression and immune activation, increased immune complex deposition, Th1 T cells and dendritic cell kidney infiltration and significant impairments in endothelial function. Modulation of TLR7 expression was observed in the Tlr9 -/- mice. Conclusions: These findings further underscore the protective role of TLR9 in TLR7-driven autoimmunity and also in the development of vasculopathy, further strengthening the importance of tightly manipulating TLRs in putative therapeutic strategies. This study provides a new model of accelerated lupus phenotype driven by danger-associated molecular patterns.